Corrigendum: Liftings of Jordan and Super Jordan Planes. Issue 2 (14th May 2022) - Andruskiewitsch, Nicolás; Angiono, Iván; Heckenberger, István
Abstract: We complete the classification of the pointed Hopf algebras with finite Gelfand-Kirillov dimension that are liftings of the Jordan plane over a nilpotent-by-finite group, correcting the statement in [N. Andruskiewitsch, I. Angiono and I. Heckenberger, Liftings of Jordan and super Jordan planes, Proc. Edinb. Math. Soc., II. Ser. 61(3) (2018), 661–672.].